The Effect of Local Renin Angiotensin System in the Common Types of Cancer - Almutlaq, Moudhi; Alamro, Abir Abdullah; Alamri, Hassan S.; Alghamdi, Amani Ahmed; Barhoumi, Tlili (Frontiers in Endocrinology, 2021)
The Renin Angiotensin System (RAS) is a hormonal system that is responsible for blood pressure hemostasis and electrolyte balance. It is implicated in cancer hallmarks because it is expressed locally in almost all of the body’s tissues. In this review, current knowledge on the effect of local RAS in the common types of cancer such as breast, lung, liver, prostate and skin cancer is summarised. The mechanisms by which RAS components could increase or decrease cancer activity are also discussed. In addition to the former, this review explores how the administration of AT1R blockers and ACE inhibitors drugs intervene with cancer therapy and contribute to the outcomes of cancer.